Mobilisation of forest bioenergy in the boreal and temperate biomes : challenges, opportunities and case studies /: challenges, opportunities and case studies. ([2016]) - Thiffault, Evelyne; Smith, Charles Tattersall; Junginger, Martin; Saddler, Jack N; Berndes, Göran
No abstract available